2017
DOI: 10.1159/000478662
|View full text |Cite
|
Sign up to set email alerts
|

Role of Next-Generation Sequencing as a Diagnostic Tool for the Evaluation of Bone and Soft-Tissue Tumors

Abstract: Bone and soft-tissue tumors are in general rare. Diagnosing these tumors is challenging based on the significant number of different tumor entities, the rareness of these tumors, and the considerable morphological heterogeneity which can be found within a single tumor entity. Considering that more than half of the described soft-tissue tumors and approximately 25% of the bone tumors harbor recurrent genetic alterations, the use of auxiliary molecular examinations should be strongly considered. Molecular analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 95 publications
0
21
0
Order By: Relevance
“…These studies revealed an EWSR1 gene rearrangement at 22q12 (Figure A). Subsequently, tissue was referred to another institution in an attempt to identify the partner gene via the Archer DX platform (ArcherDX Inc., Boulder, Colorado), utilizing massively parallel next‐generation RNA sequencing by synthesis using semiconductor technology on a Personal Genomics Machine (Ion Torrent/Thermo Fischer Scientific, Waltham, Massachusetts) . The results indicated an EWSR1‐PBX3 gene fusion in which exon 7 of EWSR1 (reference gene accession number NM_001163286) was fused in‐frame to exon 5 of PBX3 (reference gene accession number NM_001134778) (Figure B).…”
Section: Case Reportmentioning
confidence: 99%
“…These studies revealed an EWSR1 gene rearrangement at 22q12 (Figure A). Subsequently, tissue was referred to another institution in an attempt to identify the partner gene via the Archer DX platform (ArcherDX Inc., Boulder, Colorado), utilizing massively parallel next‐generation RNA sequencing by synthesis using semiconductor technology on a Personal Genomics Machine (Ion Torrent/Thermo Fischer Scientific, Waltham, Massachusetts) . The results indicated an EWSR1‐PBX3 gene fusion in which exon 7 of EWSR1 (reference gene accession number NM_001163286) was fused in‐frame to exon 5 of PBX3 (reference gene accession number NM_001134778) (Figure B).…”
Section: Case Reportmentioning
confidence: 99%
“…Immunohistochemical analysis has played little role in the diagnosis of bone tumors, although recent molecular advances have provided pathologists with specific targets amenable to antibody interrogation in some tumors such as giant cell tumor of bone and chondroblastoma [17] . Polymerase chain reaction (PCR) [18][19][20] and, more recently, massively parallel next generation sequencing (NGS) based assays have provided additional tools for assessing molecular alterations in bone tumors [21][22][23] . However, it is worth noting that many of these ancillary testing modalities are exquisitely sensitive to conventional processing techniques, particularly decalcification, and care must be taken when processing bony lesions with consideration for downstream testing that may take place after the histopathological examination.…”
Section: Introductionmentioning
confidence: 99%
“…Gene fusions are an important category of driver mutations in paediatric sarcomas [1]. While well-characterized and commonly occurring gene fusions can be identified by standard laboratory assays such as FISH and RT-PCR, an advanced technique such as next-generation sequencing (NGS) is often required to identify rare or novel gene fusions [2]. Gene fusion identification serves to confirm a pathological diagnosis, and is also important in relation to treatment as certain gene fusions have drug-targetable domains [3].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we report clinical, pathological and molecular features of three unique epidural sarcomas presenting with neurological compromise located in the cranium and spine. We describe the use of a next-generation sequencing-based assay (Archer FusionPlex Sarcoma assay (ArcherDX, Inc)) as a technique to identify gene fusions in these three primary paediatric epidural sarcomas [2, 4, 5].…”
Section: Introductionmentioning
confidence: 99%